2011
DOI: 10.1590/s0066-782x2011005000026
|View full text |Cite
|
Sign up to set email alerts
|

Acesso radial em intervenções coronarianas percutâneas: panorama atual brasileiro

Abstract: Background: Although the radial approach offers an unquestionable result in terms of reduction of vascular complications and occurrence of severe bleeding in comparison to the femoral approach, so far it has only been used in few centers which elected it as the preferential access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 19 publications
(16 reference statements)
0
8
0
2
Order By: Relevance
“…s ince its introduction into interventional cardiology, 1,2 the use of the radial access has grown steadily in recent years. 3 The advantages of the radial access route include lower rates of bleeding and vascular complications, 4-8 as well as more comfort for patients, with a significant reduction in hospital costs and length of hospitalization. 9 Some studies have even shown a reduction in mortality in certain subgroups of patients.…”
Section: Resultsmentioning
confidence: 99%
“…s ince its introduction into interventional cardiology, 1,2 the use of the radial access has grown steadily in recent years. 3 The advantages of the radial access route include lower rates of bleeding and vascular complications, 4-8 as well as more comfort for patients, with a significant reduction in hospital costs and length of hospitalization. 9 Some studies have even shown a reduction in mortality in certain subgroups of patients.…”
Section: Resultsmentioning
confidence: 99%
“…Estudos prévios demonstram que no início da aprendizagem os insucessos com a técnica e a necessidade de crossover para a técnica femoral são relativamente frequentes. 7,12 No cenário nacional, a utilização da técnica radial foi recentemente demonstrada por Andrade et al 16 com dados da Central Nacional de Intervenções Cardiovasculares (CENIC). Esses autores demonstraram que, apesar da redução significativa das complicações vasculares, a via radial foi utilizada em apenas 12,6% dos procedimentos entre os anos de 2005 e 2008.…”
Section: Discussionunclassified
“…The advantages of this approach include lower bleeding and vascular complication rates, and greater patient comfort, with a significant reduction in hospital costs and length of stay. 6,7 The higher radiological exposure via radial access compared with femoral access is related to the operator's experience. 8,9 Combining ad hoc PCI with the radial technique, compared with the femoral technique, provides more comfort for the patient, and reduces hemorrhagic complications and costs.…”
Section: Introductionmentioning
confidence: 99%